(untitled) (Research, Society and Development, 2022)
The following article show the classic diagnosis and some advances in paracoccidioidomycosis, an infectious disease with a spectrum of acute, subacute, or chronic evolution caused by the fungus Paracoccidioides spp. The disease is contracted through inhalation of an airborne fungal particles, having as main symptoms, cough, shortness of breath, weight loss and skin or mucous membrane lesions. Clinical symptoms make a correct diagnosis difficult, given the similarity with other diseases, such as tuberculosis and sarcoidosis, in addition to the fact that in some situations there may be an extended period between the individual’s exposure to the fungus and the manifestation of symptoms. Taking this into account, the aim of this work is to evaluate and discuss diagnostic methods, as well as identify new advances made by molecular, serological, mycological, and histopathological methods for this mycosis. For this purpose, a reading of case studies, an experimental essay and a systematic review were carried out.